Recommendations for Business Process Optimization in Coffee Shop MSMEs - Atfikal Umam, Muhammad Arjuna Lutfy; Ilham, Ilham (ProBisnis : Jurnal Manajemen, 2024)
A breakthrough that has been widely discussed, namely MSMEs, especially in Indonesia, are now innovating and growing rapidly. It should be noted that MSMEs (Micro, Small and Medium Enterprises) are small or medium-class businesses or businesses carried out by someone, whether it is offering goods or services. The Mas Bray Coffee Shop is included in MSMEs engaged in Food And Bavarage And of course, every business entity or MSMEs needs to pay attention to Business Process Management (BPM) so that the business processes in it can be controlled or managed properly. In the discussion, it will be described how the business processes in Coffee Shop Mas Bray from the identification process to the analyst process and the redesign process, which will later be used as a recommendation for optimizing the current business process.